Unconditional basic income and parasitism tax as nonconventional tools of state income politics - V. Ostapenko (Publishing House of the State University of Management, 2016)
Characteristics of model of the unconditional basic income and parasitism tax are considered, economic and social consequences of payments of the unconditional basic income and collection of a tax on parasitism are defined, their connection with other tools of a state policy of the income is established.